A palavra cantada nos espaços intersubjetivos de um centro de atenção psisossocial do município do Natal/RN - Fernandes, Rafaella Leite (2010)
The psychiatric care and mental health are undergoing constant change over the History. The Brazilian Psychiatric Reform, which brings up the deinstitutionalization as a structuring in the restorative care process. The Reform has as one of the mainly substitutive services the Centers for Psychosocial Care (CAPS), which work from the Singular Therapeutic Project (PTS) in order to restore the autonomy and restore the dignity of users. The therapeutic workshop is some of the resources used and work several kinds of activities as: writing, handcraft, music, poetry, and so forth. This study set up to apprehend the social representations of helping of the music workshop carried out in the CAPS II east of Natal/RN, from the reports given by the participants of the workshop, using the focal group as technique. This is a descriptive exploratory study with a qualitative approach. A total of 16 users participated in four musical therapeutic workshops from April to May 2010. The study was approved by the Ethics and Research Committee of UFRN. The discursive material from the workshop was submitted to the informational resource of Analyse Lexicale par Contexte d um Ensemble de Segments de Texte, ALCESTE, and analyzed based on the Theory of Representations and the Central Core Theory. The majority of subjects were men (62.5%), single (62.5%), aged 40-49 years (37.6%) and elementary school level (56.2 %). The reports were transcribed and submitted to the classification system of ALCESTE, which elected the following categories: Category 1 - Experience in the Word Family Sung, Category 2 - Musical Experiences and Approaches, and Category 3 - Feelings and emotions evoked by music. The representation of these individuals is anchored in the experience they have with the CAPS, lived and socialized by common sense, through this particular social group workshop objectified in music therapy as a therapeutic modality enjoyable. The central core revealed the intrinsic relationship between users and the music, establishing a relationship of openness to use the same while its therapeutic use in workshops of substitute services for mental health. Peripherals elements issues are related to listen, share and experience music in the family. Intermediary Elements relate to the feelings and emotions evoked by music, given her close relationship with it. It was found in the study that music can be construed as an artifact of good therapeutic responsiveness to users, configuring it as an invigorating and enjoyable therapy, confirming the need for continuity of this activity, as well as its expansion into the service